SELF IMAGE CONGRUITY AND CUSTOMER PERCEIVED SQ ON IMPACT SATISFACTION ON REPURCHASE INTENTION - Foster, Bob (Journal Sampurasun : Interdisciplinary Studies for Cultural Heritage, 2019)
The purpose of this research is to find out how the effect of Self Image Congruity and Customer Perceived Service Quality on Customer satisfaction has an impact on Repurchase Intention. In this study, the author took the object on the product at Alisha Fancy Shop. Based on the calculations performed, the sample used in this study amounted to 100 respondent. Analysis is carried out by the path analysis method. To clarify the variables studied, from what was formulated in the description above, that the subject matter under study is Self Image Congruity (X1), Customer Perceived Service Quality (X2), Customer satisfaction (Y), and Repurchase Intention (Z). From the results, there is a study which found that the Self Image Congruity and Customer Perceived Service Quality variables simultaneously have a significant effect on Customer satisfaction; partially the Self Image Congruity and Customer Perceived Service Quality variables have a significant effect on Customer satisfaction with a positive direction. In addition, the Self Image Congruity, Customer Perceived Service Quality, and Customer satisfaction variables also have an influence on Repurchase Intention simultaneously; partially the Self Image Congruity and Customer satisfaction variables have a significant effect on Repurchase Intention in a positive direction, while the Customer Perceived Service Quality variable is not significant effect on Repurchase Intention. Indirectly the Self Image Congruity variable and the Customer Perceived Service Quality have an influence with a positive direction towards Repurchase Intention.